High Expression of MYL9 Indicates Poor Clinical Prognosis of Epithelial Ovarian Cancer - Deng, Yuao; Liu, Longyang; Feng, Weifeng; Lin, Zhongqiu; Ning, Yingxia; Luo, Xin (Recent Patents on Anti-Cancer Drug Discovery, 2021)
Background: The prognosis of Epithelial Ovarian Cancer (EOC) is poor, but the prognostic biomarkers are neither sensitive nor specific. Therefore, it is very important to search novel prognostic biomarkers for EOC. Objectives: The present study aimed to investigate Myosin Light Chain 9(MYL9) expression in Epithelial Ovarian Cancer (EOC) tissues (including paraffin-embedded and fresh tissue samples) and its relationship with clinicopathological characteristics, as well as its potential prognostic value in patients with EOC. Methods: Between March 2009 and December 2018, all of 184 paraffin-embedded cancer tissues from patients with EOC and 41 paratumor tissues, pathologically confirmed at the Memorial Hospital of Sun Yat-sen University and Integrated Hospital of Traditional Chinese Medicine, Southern Medical University, were collected for the present study and were assessed for MYL9 protein expression patterns using Immunohistochemistry (IHC). Furthermore, from August 2013 to November 2019, 16 fresh EOC tissues and their paired paratumor tissues, pathologically confirmed at the Integrated Hospital of Traditional Chinese Medicine, Southern Medical University were analyzed using Reverse-Transcription Quantitative PCR (RT-qPCR) to detect MYL9 mRNA expression levels. Results: The results showed that MYL9 expression was higher in cancer tissues compared with that in paratumor tissues, and MYL9 overexpression was associated with shorter Recurrence Free Survival (RFS) and Overall Survival (OS) of EOC patients. Furthermore, multivariate Cox model analysis indicated that MYL9 overexpression was an independent poor survival prediction in patients with EOC. Conclusion: MYL9 is upregulated in EOC and may serve as a useful patent of prognostic biomarker in EOC, and it may demonstrate an important value for the clinical treatment and supervision of patients with EOC.
Keywords: biomarkers